Media Pembelajaran Hewan Penghasil Listrik dengan Pemanfaatan Teknologi Augmented Reality untuk Siswa SMP - Miftahul Madani; Hendri Hamzanwadi; Melati Rosanensi; Danang Tejo Kumoro (Sekawan Institut, 2024)
Augmented reality technology is a virtual object that can provide information to help users carry out work related to this technology. The learning process applied to students at SMPN 1 Praya Tengah with the theme of introducing electricity-producing animals with a learning method using printed books and verbal explanations using a whiteboard as a learning medium so that students cannot see pictures of electricity-producing animals. This research is aimed at producing more interactive learning media in introducing electricity-producing animals by using augmented re-ality technology at SMPN 1 Praya Tengah to increase interest in learning. The methodology used is the MDLC method which uses 6 stages, namely the concept, design, material collection, manu-facturing, testing and distribution stages which are implemented in learning media. The results obtained are interactive learning media on how to recognize electricity-producing animals using augmented reality which can be run on desktop-based computers. The conclusion obtained from this research is that the application of a learning media application to introduce electrici-ty-producing animals using augmented reality technology for students at SMPN 1 Praya Tengah can help students learn about electricity-producing animals in real time or in the form of 3-dimensional objects and animations. The test results used a test scale, namely a Likert scale with a value of 45.25 which can be categorized as Strongly Agree.